English Achievement and Bullying In Junior High School Students - Amalia Rahmawati; Dewi Hartinah; Faza Ilya (EDUVELOP, 2021)
This is mixed method research with qualitative and quantitative data. The qualitative comes from correlation analysis, while the quantitave data comes from interview data. The population of this study is 230 students with 146 students as sample. They come from class VII SMP Muhammadiyah Kudus. This research was bivariate analysis with Spearmen Rank Test and the instruments were in-depth interview, questionnaires, the daily test scores in English. The result of quantitative data showed that there was a moderate correlation between bullying behavior and English achievement for junior high school students with p Value = 0.000 <α 0.05 and r value -0.470 with moderate strength and having negative relationship direction. The bullying affects the English achievement in term of motivation to study English. Based on qualitative data, the students become embarrassed and afraid when they speak and learn English. This condition happens because their friends and teacher mock them. It can be concluded that there is a correlation between bullying and English achievement for Junior High School.